Analisis varians biaya dalam mengukur efektivitas pengendalian biaya operasional pada Usaha Fellow Coffee Manado - Pangaribuan, Bintang Krisdayanti; Tirayoh , Victorina Z.; Mintalangi , Syermi S. E. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Cost variance is the difference between budgeted costs and actual costs incurred.  Operating costs are the expenses incurred by an organization to carry out its activities.  When variances occur, controlling the costs associated with these variances is very important for the sustainability of business operations.  Fellow Coffee Manado, as the object of research, is a cafe that sells coffee and non-coffee beverages as well as heavy meals.  The purpose of this research is to measure the effectiveness of operational cost control at Fellow Coffee Manado using cost variance analysis. The research method used is qualitative descriptive, which aims to describe the effectiveness of operational cost control at Fellow Coffee Manado through cost variance analysis. The results of this study indicate the presence of cost variance in several components of operational costs, both favorable and unfavorable variances (unfavorable).  The operational costs for the year 2023 that experienced unfavorable variances occurred in October, while favorable variances took place from January to September and from November to December.  The causes of the variances in these costs should also be noted.  For the control of the company's operating costs to be good and effective, it is due to the preparation of the budget and efforts to improve the budget and actual performance of Fellow Coffee Manado. The researcher hopes that in the future, the company will continue to prepare a better budget, along with monitoring and evaluation.